Effect Of Ethanol Concentration In Waru Leaf Extract (Hibiscus Tiliaceus L.) On Lead Levels Of Metal (Pb) Using Atomic Absorption Spectrophotometry - Susanti, Maria Mita (Media Farmasi Indonesia, 2023)
Waru leaves are able to absorb lead in the air so that it has the potential to accumulate lead. Lead is a heavy metal that is toxic, originating from exhaust gases from motor vehicles and industry. Waru leaves can be used as a traditional medicinal plant by taking the active compounds in extract preparations. The solvent used in the manufacture of the extract is ethanol because it is a polar solvent which can potentially reduce Pb metal which is polar. This study aims to determine the effect of ethanol concentration as a solvent in waru leaf extract (Hibiscus tiliaceus L.) on Pb levels using Atomic Absorption Spectrophotometry (AAS). This research is an experimental research. The independent variable in this study was the variation in ethanol concentration while the dependent variable in this study was Pb levels. The extraction method used was remaceration with 96% ethanol, 70% ethanol and 50% ethanol and the samples were tested quantitatively by atomic absorption spectrophotometry. The lowest lead content in hibiscus leaves was hibiscus leaf extract with 70% ethanol solvent of 0.053 mg/kg. Statistical results using the Oneway ANOVA test obtained a sig value of 0.475 (p>0.05) so that there was no significant effect of variations in the concentration of 50% ethanol, 70% ethanol and 96% ethanol in hibiscus leaf extract on levels of heavy metal Pb.